GARRI PRODUCTION IN IDOMALAND, NORTH CENTRAL NIGERIA: CHALLENGES AND PROSPECTS - Samuel Alegwu Omanchi; Godwin Adadu Ogaba (International Studies Journal)
Cassava, an edible root crop and a reliable and relatively inexpensive source of carbohydrate, iswidely grown and processed into different foods such as cassava flour and garri. The main thrust of the paper is to irradiate garri production in Idomaland, North Central Nigeria,with a focus on the challenges and prospects of garri production in the area.To achieve this, anthropological and historical methodologies were used to generate data, while the qualitative method was used for the analysis. Supplementary secondary sources were also used. The paper examines the nature of garri production in Idomaland and the challenges of garri production in the area. It also highlights the prospects of garri production in the area. The paper concludes by submitting thatthe government has a role to play in forming strong policies that will favour the production of cassava and processing it into garri, flour, bread, starch among others.